MANGRARA BANUA MERAWAT MEMORI ORANG TORAJA (UPACARA PENAHBISAN TONGKONAN DI TORAJA, SULAWESI SELATAN) - Imanuella, Susia Kartika (Universitas Hasanuddin, 2017)
Tongkonan, as a house and identity marker, also serves as the center of all activities inTorajans‟ life. Tongkonan can not run its roles and functions without a consecration ceremony,namely Mangrara Banua. Mangrara Banua is a ritual for newly completed or renovatedTongkonan. Through ethnographic methods, this consecration ceremony is known not only asa housewarming ceremony for Tongkonan, more than that, Mangrara Banua is exist to answerthe needs of the Torajans about their existence as a group of indigenous peoples.Keywords:Mangrara Banua; Tongkonan; Consecration Ceremony; Memory; The Toraja.